2018
DOI: 10.1038/s41398-018-0329-x
|View full text |Cite
|
Sign up to set email alerts
|

A case–control genome-wide association study of ADHD discovers a novel association with the tenascin R (TNR) gene

Abstract: It is well-established that there is a strong genetic contribution to the aetiology of attention deficit hyperactivity disorder (ADHD). Here, we employed a hypothesis-free genome-wide association study (GWAS) design in a sample of 480 clinical childhood ADHD cases and 1208 controls to search for novel genetic risk loci for ADHD. DNA was genotyped using Illumina’s Human Infinium PsychArray-24v1.2., and the data were subsequently imputed to the 1000 Genomes reference panel. Rigorous quality control and pruning o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

4
18
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(25 citation statements)
references
References 54 publications
(47 reference statements)
4
18
0
Order By: Relevance
“…To the best of our knowledge, the study involving biological processes of TNR in uid intelligence is still less. Although indirect, our "TNR-Fluid intelligence" GWGIS nding, combined with ndings reported for other psychiatric disorders [37,38,41], supporting the evidence of TNR in the aetiology of psychiatric conditions.…”
Section: Discussionsupporting
confidence: 81%
See 1 more Smart Citation
“…To the best of our knowledge, the study involving biological processes of TNR in uid intelligence is still less. Although indirect, our "TNR-Fluid intelligence" GWGIS nding, combined with ndings reported for other psychiatric disorders [37,38,41], supporting the evidence of TNR in the aetiology of psychiatric conditions.…”
Section: Discussionsupporting
confidence: 81%
“…Interestingly, the TNR gene located within this region (1q25.1-q25.2). Additionally, genome-wide association analysis found a novel association of ADHD and with TNR gene [38]. In another study, researchers found TNR de ciency would cause an early onset and nonprogressive neurodevelopmental disorder [41].…”
Section: Discussionmentioning
confidence: 98%
“…To the best of our knowledge, the study involving biological processes of TNR in uid intelligence is still less. Although indirect, the "TNR-fluid intelligence" of GWGIS nding, combined with ndings reported for other psychiatric disorders [37,38,41], supporting the evidence of TNR in the aetiology of psychiatric conditions.…”
Section: Discussionsupporting
confidence: 61%
“…It can be inferred that RP11-388P9.2 might affect the CFTR expression by regulating has-miR-114-3p, further affecting the amniotic fluid content of pregnant women. Moreover, TNR can interact with fibronectin 1, which can be involved in cell migration and adhesion biological processes including embryogenesis [ 31 ]. Tenascin is also produced in the extracellular matrix of cultured amnion epithelial cells [ 32 ].…”
Section: Discussionmentioning
confidence: 99%